The 'G' men: a profile of GBL/GHB users in an area of high drug-related mortality. (11th August 2014) - Durgahee, S.; Allen, G.; Williams, H.
Abstract : Objectives: Gamma-butyrolactone/gamma-hydroxybutyrate (GBL/GHB) and related analogues are increasingly misused. The study reports on patient characteristics, nature and pattern of use, complications and comorbidity for a cohort of patients presenting to a large Substance Misuse Service in Brighton and Hove City. Method: A retrospective case-note review of routinely collected clinical data on patients with primary GBL/GHB misuse. Results: In all, 24 individuals were male and 3 female, with a mean age of 34 years. A total of 21 males identified themselves as gay and 1 female as bisexual. Just over half (15, 56%), respectively, were living in stable accommodation and were in employment or third-level education. In all, 22 (81%) met criteria for physical dependence and two-thirds (18, 67%) had experienced overdose. The group was using large amounts of GBL (mean 53 ml/day) with a significant number (25, 93%) using 'around the clock' (every 1–3 hours). Over one-third (10, 37%) had a diagnosis of HIV and with 24 (89%) having a presumptive diagnosis of anxiety disorder. Conclusions: A profile of gay men with relatively stable lifestyles, but nevertheless with a high rate of complication of GBL/GHB use and with a significant comorbidity (HIV and psychological problems) was identified. The need for integrated specialist services and the importance of liaison with Emergency Departments and HIV services is highlighted.